UPAYA MENINGKATKAN HASIL BELAJAR SISWA MELALUI PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) - Puji Yanti; Pramudiyanti Pramudiyanti; Rini Rita T Marpaung (Jurnal Bioterdidik: Wahana Ekspresi Ilmiah, 2014)
This study was aimed to find out the influence of applicating cooperative learning model type NHT towards improvement of students learning activities and outcomes. The research designs was non equivalent pretest – posttest. The research sample were students in VIIA and VIIB class that was selected by cluster random sampling. Data of the research were qualitative and quantitative. The qualitative data was gotten by students learning activity and questionnaire that was analyzed descriptively. The quantitative data was the average score of test, that was analyzed by t-test and U-test. The result of this study shown that the average of students outcomes in experimental class are higher than control (experiment= 77.60; control = 49.10). The average of student learning activities percentage in all observed aspects in experimental class shown higher enhancement than control (experiment = 60.40; control = 56.30). In addition, the students also gives positive responses to applicating cooperative learning model type NHT. Penelitian ini bertujuan untuk mengetahui penerapan model pembelajaran NHT terhadap peningkatan aktivitas dan hasil belajar oleh siswa. Desain penelitian adalah pretes-postes tak ekuivalen. Sampel penelitian adalah siswa kelas VIIA dan VIIB yang dipilih secara cluster random sampling. Data penelitian berupa data kualitatif dan kuantitatif. Data kualitatif diperoleh dari aktivitas belajar siswa dan angket tanggapan siswa yang dianalisis secara deskriptif. Data kuantitatif diperoleh dari rata-rata nilai tes yang dianalisis menggunakan uji-t dan uji-U. Hasil penelitian menunjukkan hasil belajar  kelas eksperimen lebih tinggi (eksperimen = 77,60; kontrol = 49,10). Rata-rata persentase aktivitas siswa semua aspek kelas eksperimen juga menunjukkan peningkatan yang lebih tinggi (eksperimen = 60,40; kontrol = 56,30). Selain itu, semua siswa memberikan tanggapan positif terhadap penggunaan model pembelajaran NHT. Kata kunci: aktivitas belajar, hasil belajar, numbered head together.